Performance analysis of variable weight Optical Code Division Multiple Access System - Kharazi, Seyedmohammadsaleh Seyedzadeh (2013)
Recently, Optical Code Division Multiple Access (OCDMA) systems are among the popular choice of research areas deployed in metro networks as they could provide service differentiation for different quality of signals in such networks. In OCDMA system Quality of Service (QoS) differentiation is realized by assigning dierent code weight or length for each user or service. In actual implementation which involves ber in the transmission, the ber impairment such as dispersion and nonlinear effects can greatly reduce the performance of the system, especially when the bit rate is high. In this thesis, mathematical and simulation model is proposed to analyze the performance of a Variable-Weight OCDMA (VW-OCDMA) system. The research was carried out by firstly developing a mathematical model for VWOCDMA system deploying Direct Detection (DD) and AND detection techniques. In the numerical analysis the effects of phase-induced intensity noise, shot noise and thermal noise was taken into account. Subsequently, different detection schemes i.e. DD and AND subtraction, as well as different optical sources i.e. broadband and laser were analyzed using software simulation. Three weights of 2, 4 and 6 were chosen for different services which represent voice, data and video. The simulationse tup was also used to investigate the effects of fiber impairments including chromatic dispersion, self-phase modulation and four wave mixing. Various dispersion compensation techniques were then applied in VW-OCDMA system. Finally,feasibility of the proposed system was investigated using practical experimentation to compare with the system’s performance in simulation environment. Three users with weight 6, 4 and 2 were used in experimental design, each transmitting data at rate of 1.25 Gbps. With reference to BER of 10−3, 10−9 and 10−12 for voice, data and video respectively, VW-OCDMA deploying DD scheme supports 95 users each operating at bit rate of 1.25 Gbps. Moreover, using non-zero dispersion shifted fiber and chirped fiber Bragg grating the signals of users can be transmitted up to 150 km.